Case study on affecting financial management at department of veterinary services Selangor / Nur Hidayati Abu Ari Jal - Abu Arijal, Nur Hidayati (2018)
Financial management played an important role in our life. Without a proper financial management, it will cause a lot of problems that might occur in the future. The mismanagement of financial will lead into a greater negative cause. This problem is continuously happen in today society. Hence, a research need to be done to view the financial management of employees at Department Management Services (Bahagian Khidmat Pengurusan), Department of Veterinary Selangor. This research involves 30respondents who had been choose randomly. This study adapts quantitative approaches where substantial academic works would be reviewed using contentanalysis from the questionnaires. This study further submits that salary, family structure are affected to financial management.